2023
DOI: 10.1080/0886022x.2023.2188088
|View full text |Cite
|
Sign up to set email alerts
|

Glomerulosclerosis is a prognostic risk factor in patients with membranous nephropathy and non-nephrotic proteinuria

Abstract: Objective To explore the predictive value of the proportion of glomerulosclerosis (GS) incidences on the progression of membranous nephropathy with non-nephrotic proteinuria (NNP). Methods This study was a single-center, retrospective, cohort study. Patients with biopsy-proven idiopathic membranous nephropathy were divided into three groups based on the proportion of glomerular sclerosis, and their demographic, clinical, and pathological data were compared. The proporti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 19 publications
0
3
0
Order By: Relevance
“…Sun et al . have reported that a high level of glomerulosclerosis was an independent risk factor for the prognosis of patients with pMN [ 20 ]. The deposition of subepithelial immune complexes in the glomerulus can affect podocyte and basement membrane attachment, and the detachment of epithelial cells and the GBM can cause glomerulosclerosis [ 36 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Sun et al . have reported that a high level of glomerulosclerosis was an independent risk factor for the prognosis of patients with pMN [ 20 ]. The deposition of subepithelial immune complexes in the glomerulus can affect podocyte and basement membrane attachment, and the detachment of epithelial cells and the GBM can cause glomerulosclerosis [ 36 ].…”
Section: Discussionmentioning
confidence: 99%
“…The ability of FETP to predict the risk of renal failure remained unchanged when known risk factors, such as age, PCR, eGFR and treatment, were considered in the multivariate analysis. Clinical factors, such as older age [ 1 , 2 , 38 ], male sex [ 1 ], serum creatinine levels [ 1 , 2 , 3 ], the severity of proteinuria [ 2 , 38 , 39 ] and hypertension [ 39 ], and histological factors, such as the degree of tubulointerstitial damage [ 39 ] and glomerulosclerosis [ 20 ], have been reported as risk factors for renal prognosis in patients with pMN. Among all the predictive variables reported in previous studies, the most frequently used and reliable indicators were proteinuria and renal function variables [ 2 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation